Transformation Of The Indonesian National Army's Doctrine And Strategy In Facing Multidimensional Threats: Towards The Vision Of Golden Indonesia 2045 - Sianturi, Kristomei; Saputro, Guntur Eko (UNIVERSITAS PAKUAN, 2025)
Indonesia's territory borders several large countries in Asia, such as China, India and Australia, making this country vulnerable to multidimensional threats. One of them is that Indonesia faces the threat of terrorism which is often related to the radicalization of extreme ideologies. Therefore, adaptive, collaborative policies and wise management of natural and human resources are needed to maintain the stability and integrity of the Unitary State of the Republic of Indonesia (NKRI), one of which is by carrying out the transformation of the doctrine and strategy of the Indonesian Army in facing multidimensional threats in order to achieve the Vision of Golden Indonesia 2045. This journal is written using a qualitative method with a descriptive analysis approach or reviewing documents by involving in-depth analysis of news, strategic or technical documents, relevant previous research and analysis of the results of sources. So that with the writing of this journal, a comprehensive analysis can be carried out on the urgency and strategy of the transformation of the Indonesian Army doctrine in facing the spectrum of multidimensional threats for the period 2024-2045 which is useful as study material in facing the dynamics of contemporary threats, the need for adaptation of doctrine and a strategic roadmap towards achieving the ideal posture of the Indonesian Army in supporting the Vision of Golden Indonesia 2045. In addition, it is also expected to realize a better, more advanced Indonesia with high global competitiveness. So to achieve this, Indonesia must be able to face major challenges in various aspects of development, ranging from economic, social, political, cultural, to environmental in order to achieve the vision of golden Indonesia 2024